2016
DOI: 10.1177/0884533615621547
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Adductor Pollicis Muscle Thickness With Clinical Outcomes in Intensive Care Unit Patients

Abstract: The results showed that APMT is a low-cost, reliable, and easy method to assess nutrition status and to predict the patient's outcomes in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 12 publications
(19 reference statements)
1
34
2
4
Order By: Relevance
“…Likewise, Bragnolo et al 27 showed that postoperative mortality was 25% higher in patients with APMT below the cut-off point considered for dominant hand in the older patients <12.2mm (women) and <14.4mm for men and Ghorabi et.al 30 in patients from intensive care unit, 11.12 ± 2 mm in the patients who died and 16.7 ± 2.2 mm in those who survived (P = .05).…”
Section: Discussionmentioning
confidence: 91%
“…Likewise, Bragnolo et al 27 showed that postoperative mortality was 25% higher in patients with APMT below the cut-off point considered for dominant hand in the older patients <12.2mm (women) and <14.4mm for men and Ghorabi et.al 30 in patients from intensive care unit, 11.12 ± 2 mm in the patients who died and 16.7 ± 2.2 mm in those who survived (P = .05).…”
Section: Discussionmentioning
confidence: 91%
“…The reason for selecting the APM thickness as a malnutrition index is that its measurement is easy and fast and has a well-defined anatomical position [9]. Two studies have shown that the APM thickness is associated with mortality in the ICU [10, 11]. The first was conducted on 248 medical and surgical patients in a tertiary care ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of thicknesses of other muscles such as triceps requires subcutaneous fat measurement and a use of a formula for calculation [9]. Two studies have reported that the APM thickness on the day of admission predicts morbidity and mortality in critically ill patients [10, 11]. If APM thickness at the time of ICU admission is sensitive to predicting outcomes, then incorporating it directly into the predictive scoring models like APACHE II and III may increase the predictive value of these models.…”
Section: Introductionmentioning
confidence: 99%
“…Some inflammatory parameters, such as IL‐6, are an integral part of the nutrition assessment score for intensive care patients (Nutrition Risk in Critically Ill [NUTRIC] score), which needs to be validated prospectively 77 . Recent clinical studies have shown an association between muscle mass measured by different techniques and survival of ICU patients 78 , 79 . Plank 80 reported the derangements in body composition of 33 patients (21 with trauma and 12 with peritonitis) over a 3‐week period from soon after admission to the ICU.…”
Section: Clinical Consequencesmentioning
confidence: 99%